Can Noise in Dental Clinic Produce Hearing Loss? - Lourenço, Edmir Américo; Berto, Janaína Medina da Rocha; Duarte, Sávio Butignolli; Greco, João Paulo Martins (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The sensorial hearing loss and irreversible noise induced is the major evitable occupational cause of hearing loss worldwide. The dentists are health professionals exposed to noises from equipment in their clinics and may suffer hearing losses.Objective: Measure the noise intensities emitted by the high rotation motors (mar) used in public and private dental clinics, check whether they are harmful for the human ear and compare the results obtained in such services.Method: Serial, retrospective study with measures of the noise intensities in dBNA with a decibelimeter Minipa MSL-1352C, USA, in four dental clinics of the public service and four private clinics in Jundiaí-SP, initially from the basal environment noise in each clinic, during five minutes and then from the noise emitted by the high rotation motor (mar) in operation during five minutes to obtain the averages.Results: Public clinics: 1)basal medium = 56.4dB;mar = 77.2dB. 2)basal medium = 61.7dB;mar = 73.7dB. 3)basal medium = 61.07dB;mar = 75.04dB. 4)basal medium = 63.6dB;mar = 77.3dB. Private clinics: 1)basal medium = 60,7dB;mar = 79,1dB.2)basal = 60,7dB;mar = 83,1dB.3)basal = 58,4dB;mar = 75,5dB.4)basal = 63dB;mar = 76dB.Conclusion: The intensities measured of noise emitted by high rotation motors used in public and private dental clinics are below the limits harmful to the auditory health. In the public service, the basal medium noise intensity is higher than that of the private clinics, however the one of the high rotation motors is higher in the private clinics.
Keywords: occupational noise; work environment; odontology; odontological instruments; hearing loss